Utilization of the Google Sites Platform in Evaluation of Basic Education Programs - Rina, Rina; Mahmudah, Fitri Nur (Lembaga Penelitian dan Pendidikan Mandala, 2023)
Technological developments have progressed and major changes have significantly impacted the world of education. Various platforms can be accessed online, one of which is Google Sites which can be used by anyone, anytime, and for free. However, various challenges are still being experienced in the process of applying Google Sites in education. The digital transformation of education is highly dependent on the capacity of available technology, the adjustment of teaching staff to technological developments, and the background of students who are also able to make an impact. The purpose of this research is to find out the use of the Google Sites platform in various educational programs. The research method used in this study is the SLR (Systematic Literature Review) method which collects data from various journals and articles. The journal content used is related to the use of Google Sites in educational programs. Based on the research results that have been carried out in the research table, it is explained that Google Sites can provide benefits in educational programs, increase student interest in learning, and hone the creativity of educators in presenting needs related to the programs being implemented.